Understanding Metaverse in Education: Connecting Metaverse to the existing Cultural Education in Indonesia (Research, Society and Development, 2023)
Communication technology develops so rapidly that it changes the forms of interaction between people. Digital interaction that brings humans together in a virtual world seems to replace face-to-face interaction that has been a human habit since ancient times. However, digital interaction through media turns out to have many shortcomings and reduce the values that characterize a society. Even so, innovation in communication technology cannot be stopped, and now there is a metaverse. A digital platform that allows man to interact in the virtual world three-dimensional. Although this technology cannot be accessed and enjoyed by all levels of society, it is possible that in the next few decades social interactions in the metaverse will dominate interactions among people. Before that happens, in-depth analysis of all sectors is needed so that humans are not immersed in a virtual world that can actually threaten their existence. This research is a phenomenological research using a philosophical perspective that focuses on the possible use of the metaverse in education. In this study, it was concluded that the use of the metaverse is currently considered unnecessary because there is no urgent reason for the use of this technology, while face-to-face learning is still the best learning method, at least until today.